2017
DOI: 10.1007/s00104-017-0412-5
|View full text |Cite
|
Sign up to set email alerts
|

Laparoskopische Resektion eines Riesenkolondivertikels

Abstract: This case report describes a laparoscopic atypical colon wedge resection as treatment of a giant colon diverticulum. Only four laparoscopic bowel resections in terms of sigmoid resections or hemicolectomy with primary anastomosis have been reported. Minimally invasive surgery can be a valuable alternative to open procedures. In the current case a laparoscopic atypical colon wedge resection was safely performed. This option might be considered as an alternative to extended resections of giant diverticula. Local… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…A laparoscopic right hemicolectomy was performed for one-stage treatment [ 3 ]. Roch et al reported that laparoscopic atypical colon wedge resection was safely performed, and it might be considered an alternative for extended resections of giant diverticula [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…A laparoscopic right hemicolectomy was performed for one-stage treatment [ 3 ]. Roch et al reported that laparoscopic atypical colon wedge resection was safely performed, and it might be considered an alternative for extended resections of giant diverticula [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other advantages include the use of immunofluorescence to assess the blood supply of the colon to determine resection margins and the integration of flexible wristed instruments allowing the surgeon more degrees of freedom for suturing [4]. These advantages overcome some of the challenges associated with open and laparoscopy can be overcome [5][6][7][8][9][10][11][12].…”
Section: Discussionmentioning
confidence: 99%
“…Some advocate for a more traditional hemicolectomy on the affected side, to reduce any chance of recurrence [ 5 ]. Others have had success with a simple wedge resection of the diverticulum [ 7 ]. Surgery can be open, laparoscopic, or robotically assisted depending on the availability of specialty equipment and surgeon experience.…”
Section: Discussionmentioning
confidence: 99%